Sharing On Suffering Experiences As The Secularity Of Incarnation - Antonius Denny Firmanto (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
The changing context of the Christian life brings Christian life at a crossroads, the first whether to remain in a comfort zone or the second whether to enter into the realm of profane daily life. The urge to get out of selfness and deal with the public world makes the Church deal with questions about its own identity. In this article, I want to explore the question of incarnation in Johan Baptist Metz's secularity. However, the concept of incarnation is applied solely to Jesus Christ as the Divine Word became flesh. Ricoeurian hermeneutics could help explain the term secularity on incarnation to immediate. And corporeal suffering of the others. The turn to Ricoeur as a methodological resource for theology provides a philosophical account of the methodology behind critical theology. The article concludes that the human being in their relationship its suffering experience is an experience of encounter.